Positive electrode active material for non-aqueous electrolyte secondary battery, method for producing same, and non-aqueous electrolyte secondary battery

By using the positive electrode active material of lithium transition metal composite oxide in a nonaqueous electrolyte secondary battery, the problem of difficulty in achieving high capacity and charge and discharge efficiency in the prior art is solved, and efficient battery performance is achieved.

CN119908038APending Publication Date: 2025-04-29PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380067239.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-12
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high capacity and improve charge and discharge efficiency in non-aqueous electrolyte secondary batteries.

Method used

The lithium transition metal composite oxide represented by the constituent formula LiαNaβNi1-b-cMnbXcOd is used as the positive electrode active material. The ratio I108/I110 of the diffraction peak of the (108) plane obtained by powder X-ray diffraction diffraction pattern is less than 0.4.

Benefits of technology

It realizes the high capacity of the non-aqueous electrolyte secondary battery while improving the charge and discharge efficiency, reduces disorder, and improves the stability of the layered rock salt structure of lithium transition metal composite oxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119908038A_ABST
    Figure CN119908038A_ABST
Patent Text Reader

Abstract

A positive electrode active material for a non-aqueous electrolyte secondary battery, which is an example of an embodiment, contains a lithium transition metal composite oxide represented by the compositional formula Li [alpha] Na [beta] Ni [1-b-c] MnbXcOd (in the formula, X is at least one element selected from the group consisting of metal elements other than Li, Na, Ni, and Mn, 0.80 < = a < = 1.20, 0 < = beta < = 0.05, 0.80 < = a + beta < = 1.20, 0.25 < b < = 0.65, 0 < = c < = 0.1, 0.4 < = 1-b-c < 0.75, and d is a value satisfying an atomic valence). The ratio I108 / I110 of the integrated intensity I108 of the diffraction peak of the (108) plane to the integrated intensity I110 of the diffraction peak of the (110) plane in an X-ray diffraction pattern obtained by powder X-ray diffraction of the lithium transition metal composite oxide satisfies I108 / I110 < 0.4.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, a method for producing the positive electrode active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery using the positive electrode active material. Background Art

[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium-ion batteries have also attracted attention as power sources for electric vehicles (EVs), hybrid electric vehicles (HEVs, PHEVs), etc., and are expected to further expand their uses. In order to use them as such power sources, further high capacity and improved charge and discharge efficiency of non-aqueous electrolyte secondary batteries are required.

[0003] As a positive electrode active material for realizing high capacity of non-aqueous electrolyte secondary batteries, lithium transition metal composite oxides containing Ni have attracted attention. For example, Patent Document 1 discloses a lithium transition metal composite oxide containing Ni, in which the half-value width of the diffraction peaks of the (108) plane and the (110) plane in powder X-ray diffraction (XRD) is less than 0.18°.

[0004] Prior Art Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2005-053764 Summary of the invention

[0006] In non-aqueous electrolyte secondary batteries, achieving high capacity and improving charge and discharge efficiency are important issues. The prior art including Patent Document 1 cannot fully address such issues and there is still much room for improvement.

[0007] An object of the present disclosure is to provide a positive electrode active material capable of realizing a non-aqueous electrolyte secondary battery having a high capacity and improved charge and discharge efficiency.

[0008] A technical solution disclosed herein relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a composition formula Li α Na β Ni 1-b-c Mn b X c O d (wherein X is at least one element selected from metal elements other than Li, Na, Ni, and Mn, 0.80≤α≤1.20, 0≤β≤0.05, 0.80≤α+β≤1.20, 0.25<b≤0.65, 0≤c≤0.1, 0.4≤1-bc<0.75, and d is a value satisfying the atomic valence) represented by a lithium transition metal composite oxide, and an integrated intensity I of a diffraction peak of a (108) plane of an X-ray diffraction pattern of the lithium transition metal composite oxide obtained by powder X-ray diffraction108 The integrated intensity I of the diffraction peak relative to the (110) plane 110 Ratio I 108 / I 110 For I 108 / I 110 <0.4.

[0009] A nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode including the positive electrode active material, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and a nonaqueous electrolyte.

[0010] According to the positive electrode active material for a nonaqueous electrolyte secondary battery according to one aspect of the present disclosure, it is possible to provide a nonaqueous electrolyte secondary battery having a high capacity and improved charge and discharge efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment.

[0012] Figure 2 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 1.

[0013] Figure 3 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 2.

[0014] Figure 4 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 3.

[0015] Figure 5 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 4.

[0016] Figure 6 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 5.

[0017] Figure 7 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 6.

[0018] Figure 8 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 7.

[0019] Fig. 9 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 8.

[0020] Fig.10This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 9.

[0021] Fig.11 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 10.

[0022] Fig.12 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 11.

[0023] Fig.13 This is a diagram showing the powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Example 12.

[0024] Fig.14 This is a diagram showing a powder X-ray diffraction pattern of the lithium-transition metal composite oxide prepared in Comparative Example 1.

[0025] Fig.15 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Comparative Example 2.

[0026] Fig.16 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Comparative Example 3.

[0027] Fig.17 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Comparative Example 4.

[0028] Fig.18 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Comparative Example 5.

[0029] Fig.19 This is a diagram showing a powder X-ray diffraction pattern of the lithium transition metal composite oxide prepared in Comparative Example 6.

[0030] Fig. 20 This is a diagram showing a powder X-ray diffraction pattern of the lithium-transition metal composite oxide prepared in Comparative Example 7.

[0031] Fig.21 This is a diagram showing a SEM image of the lithium-transition metal composite oxide produced in Example 1.

[0032] Fig. 22 This is a diagram showing a SEM image of the lithium-transition metal composite oxide produced in Comparative Example 1. DETAILED DESCRIPTION

[0033] When preparing lithium transition metal composite oxides containing Ni, mixing of Ni elements into Li sites, so-called disorder, may occur. Disorder hinders the diffusion of Li ions in the lithium transition metal composite oxide, thus causing a decrease in the charge and discharge capacity and charge and discharge efficiency of the battery.

[0034] Therefore, the present inventors conducted intensive research to solve the above-mentioned problems, and found that in a lithium transition metal composite oxide in which Li, Ni, and Mn are essential elements in the positive electrode active material, and the ratio of Ni to the total molar number of metal elements other than Li and Na is 40 mol% or more and less than 75 mol%, the integrated intensity I of the diffraction peak of the (108) plane of the X-ray diffraction pattern obtained by subjecting the composite oxide to X-ray diffraction is 108 The integrated intensity I of the diffraction peak relative to the (110) plane 110 Ratio I 108 / I 110 less than 0.4, it is possible to provide a non-aqueous electrolyte secondary battery that achieves high capacity and improves charge and discharge efficiency. 108 / I 110 When the ratio is less than 0.4, the stability of the layered rock salt structure of the lithium transition metal composite oxide is improved, and the amount of disorder generated is specifically reduced.

[0035] Hereinafter, with reference to the accompanying drawings, an example of an embodiment of a nonaqueous electrolyte secondary battery positive electrode active material and a nonaqueous electrolyte secondary battery using the active material is described in detail. In addition, a method of selectively combining the various components of the multiple embodiments and variations described below is also included in the scope of the present disclosure.

[0036] In the embodiment described below, a cylindrical battery in which a wound electrode body 14 is housed in an outer can 16 with a bottomed cylindrical shape is exemplified, but the outer body of the battery is not limited to a cylindrical outer can. As other embodiments of the non-aqueous electrolyte secondary battery disclosed herein, a square battery with a square outer can, a coin-shaped battery with a coin-shaped outer can, and a bag-type battery with an outer body composed of a laminate sheet including a metal layer and a resin layer can be cited. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked via a separator.

[0037] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer can 16 for storing the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one side open in the axial direction, and the opening of the outer can 16 is sealed by a sealing body 17. In the following, for the sake of convenience of description, the sealing body 17 side of the battery is set as the upper side, and the bottom side of the outer can 16 is set as the lower side.

[0038] The non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. The non-aqueous solvent may contain a halogen substitute in which at least a portion of the hydrogen of these solvents is replaced by a halogen atom such as fluorine. The electrolyte salt may be, for example, a lithium salt such as LiPF6, LiClO4, or LiBF4. In addition, the electrolyte is not limited to a liquid electrolyte, and may also be a solid electrolyte using a gel-like polymer or the like.

[0039] The positive electrode 11, the negative electrode 12 and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, which are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape. In order to prevent the precipitation of lithium, the negative electrode 12 is formed to be one circle larger than the positive electrode 11. In other words, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction (short side direction). The two separators 13 are formed to be at least one circle larger than the positive electrode 11, for example, arranged in a manner of sandwiching the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0040] Insulating plates 18 and 19 are disposed above and below the electrode body 14, respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.

[0041] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove 22 is formed on the outer can 16, in which a part of the side surface protrudes inward and supports the sealing body 17. The groove 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and supports the sealing body 17 on its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 by the groove 22 and the open end of the outer can 16 riveted to the sealing body 17.

[0042] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating component 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating component 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating component 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat, the lower valve body 24 is deformed and ruptured in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 ruptures, and the gas is discharged from the opening of the cover 27.

[0043] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the nonaqueous electrolyte secondary battery 10 , particularly the positive electrode 11 , will be described in detail.

[0044] [positive electrode]

[0045] The positive electrode 11 has a positive electrode current collector and a positive electrode mixture layer formed on both sides of the positive electrode current collector. The positive electrode current collector can use a foil of a metal such as aluminum or aluminum alloy that is stable within the potential range of the positive electrode 11, a thin film having the metal configured on the surface, etc. The positive electrode mixture layer contains a positive electrode active material, a conductive material, and a binding material. The positive electrode 11 can be manufactured by coating a positive electrode slurry containing a positive electrode active material, a conductive material, and a binding material on the surface of the positive electrode collector (coating process), drying the coating (drying process), rolling, and forming a positive electrode mixture layer on both sides of the positive electrode collector (rolling process).

[0046] As the conductive material contained in the positive electrode mixture layer, carbon materials such as carbon black, acetylene black, Ketjen black, carbon nanotubes (CNT), graphene, and graphite can be exemplified. As the binding material contained in the positive electrode mixture layer, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. These resins can be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc.

[0047] The positive electrode active material contained in the positive electrode mixture layer has a layered structure and includes a lithium transition metal composite oxide containing at least Ni and Mn.

[0048] Lithium transition metal composite oxides have the composition formula Li α Na β Ni 1-b-c Mn b X c O d (wherein, X is at least one element selected from metal elements other than Li, Na, Ni, and Mn, 0.80≤α≤1.20, 0≤β≤0.05, 0.80≤α+β≤1.20, 0.25<b≤0.65, 0≤c≤0.1, 0.4≤1-bc<0.75, and d is a value satisfying the atomic valence). The composite oxide is a composite oxide containing Li, Ni, and Mn as essential elements, and the ratio of Ni to the total molar number of metal elements other than Li and Na is 40 mol% or more and less than 75 mol%.

[0049] In the above composition formula Li α Na β Ni 1-b-c Mn b X c O d , the total molar ratio of Li and Na (α+β) is 0.80≤α+β≤1.20, preferably 0.9≤α+β≤1.15. The molar ratio of Ni (1-bc) is 0.4≤1-bc<0.75, preferably 0.4≤1-bc≤0.7, more preferably 0.45≤1-bc≤0.6, and further preferably 0.45≤1-bc≤0.55. The molar ratio of Mn (b) is 0.25<b≤0.65, preferably 0.3≤b≤0.6, more preferably 0.4≤b≤0.55, and further preferably 0.45≤b≤0.55. If the molar ratio of Li, Ni and Mn is within this range, it is easy to increase the charge and discharge capacity of the battery and improve the charge and discharge efficiency. The molar ratio of O (d) is a value that satisfies the atomic valence.

[0050] In the above composition formula Li α Na β Ni 1-b-c Mn b X c O dIn the embodiment of the present invention, the molar ratio (β) of Na is 0≤β≤0.05, preferably 0≤β≤0.035. By the presence of a trace amount of Na, the layered structure of the composite oxide is stable, and it is easier to achieve a high capacity of the battery. In addition, if the molar ratio of Na exceeds 0.05, Na ions are extracted from the positive electrode during charging, and the extracted Na ions are likely to be absorbed by the negative electrode. As a result, by-products are generated by reacting with the nonaqueous electrolyte during charging and discharging, which is the main reason for the reduction of the charge and discharge capacity and charge and discharge efficiency of the battery.

[0051] In the above composition formula Li α Na β Ni 1-b-c Mn b X c O d In the above, X is at least one element selected from metal elements other than Li, Na, Ni, and Mn. In addition, X is preferably at least one element selected from Mg, Ca, Sr, Ba, Sn, Ti, Si, V, Cr, Fe, Cu, Zn, Bi, Sb, B, Ga, In, P, Zr, Hf, Nb, Ta, Mo, W, Co, and Al, and more preferably Al, Co, Zr, or P. The molar ratio (c) of X is 0≤c≤0.1, preferably 0≤c≤0.05, and more preferably 0≤c≤0.03. By containing X in the lithium transition metal composite oxide, it is easy to achieve a high capacity of the battery.

[0052] The positive electrode active material is mainly composed of the composite oxide represented by the above composition formula. Here, the main component refers to the component with the highest mass ratio among the constituent components of the composite oxide. In the mixture layer of the positive electrode 11, as the positive electrode active material, a composite oxide other than the composite oxide represented by the above composition formula can be used in combination, but the content of the above composite oxide is preferably 50% by mass or more, and can be 100% by mass in essence. In addition, the composition of the composite oxide can be measured using an ICP emission spectrophotometer (e.g., iCAP6300 manufactured by Thermo Fisher Scientific).

[0053] The lithium transition metal composite oxide is, for example, a secondary particle formed by the aggregation of multiple primary particles. An example of a volume-based median particle size (D50) of the lithium transition metal composite oxide is 1 to 30 μm, or 3 to 20 μm. D50 is the particle size at which the volume cumulative value is 50% in the particle size distribution measured by a laser diffraction scattering method. The BET specific surface area of ​​the lithium transition metal composite oxide is, for example, 0.1 to 10 m 2 / g, or 0.5~5m 2 When the BET specific surface area is within this range, a high capacity can be easily achieved. The BET specific surface area is measured according to the BET method (nitrogen adsorption method) described in JIS R1626.

[0054] The integrated intensity I of the diffraction peak of the (108) plane in the X-ray diffraction pattern of the lithium transition metal composite oxide obtained by X-ray diffraction is 108 The integrated intensity I of the diffraction peak relative to the (110) plane 110 Ratio I 108 / I 110 For I 108 / I 110 <0.4. If I 108 / I 110 is less than 0.4, the disorder amount in the layered rock salt structure of the lithium transition metal composite oxide is specifically reduced. In other words, if I 108 / I 110 When the ratio is 0.4 or more, the disorder in the layered structure of the lithium transition metal composite oxide increases. 108 / I 110 If the ratio is 0.4 or more, the stability of the layered structure of the lithium transition metal composite oxide decreases. 108 / I 110 When the ratio is less than 0.4, the charge and discharge capacity of the battery can be increased and the charge and discharge efficiency can be improved.

[0055] Here, the X-ray diffraction pattern can be obtained using a desktop X-ray diffraction device (manufactured by Rigaku Corporation, trade name "MiniFlex600"). At this time, the diffracted X-rays are detected with a high-speed one-dimensional detector (D / teX Ultra2). In addition, the measurement conditions of the above-mentioned X-ray diffraction device are set as follows: the X-ray source is CuKα rays, the tube voltage is 40kV, the tube current is 15mA, the divergence slit (DS) is 0.625°, the scattering slit (SS) is 13mm (open), the light receiving slit (RS) is 8mm, the scanning axis is 2θ / θ, the scanning method is a continuous mode, the 2θ scanning range is 10-80°, the scanning speed is 10° / min, and the step width is 0.02°. In addition, the X-ray diffraction measuring device and the X-ray diffraction measuring conditions are not limited to the above conditions.

[0056] In the data obtained by the above-mentioned X-ray diffraction measurement, the scanning angle 2θ is set to x, and the pseudo-Voigt function of formula (3) composed of the linear sum of the Lorentz function shown in formula (1) and the Gaussian function shown in formula (2) is fitted. By fitting, the peak height h, peak position u, standard deviation w, component η of the Lorentz function, and component (1-η) of the Gaussian function are obtained. The value of the product of the peak height h obtained by fitting and the standard deviation w is used as the integrated intensity, and the integrated intensity under each reflection index is calculated. In addition, by using a computer (such as a personal computer) equipped with a CPU, ROM, RAM, HDD, and various interfaces, it is possible to achieve fitting based on the pseudo-Voigt function. Furthermore, for example, the processing can be performed by installing the solver function of Microsoft's Excel or the nonlinear fitting function of Lightstone's Origin on the computer. In addition, dedicated software for analysis (such as SmartLab Studio II, a comprehensive X-ray analysis software manufactured by Rigaku Corporation, or the "RIETAN-FP" program (F. Izumi and K. Momma, Solid State Phenom., 130, 15-20 (2007))) can also be installed, and the above processing can be performed by executing the software. Furthermore, the fitting processing is not limited to the above method.

[0057]

[0058] h(x)=ηf(x)+(1-η)g(x) Formula (3)

[0059] The integrated intensity I of the diffraction peak of the (003) plane of the X-ray diffraction pattern of the lithium transition metal composite oxide obtained by the above X-ray diffraction is 003 The integrated intensity I of the diffraction peak relative to the (104) plane 104 Ratio I 003 / I 104 Preferably 1 003 / I 104 >1.0. If I 003 / I 104 When the ratio is 1.0 or less, the stability of the layered structure of the lithium transition metal composite oxide decreases, and the charge and discharge efficiency of the battery decreases.

[0060] The half-value width of the diffraction peaks of the (108) plane and the (110) plane of the X-ray diffraction pattern obtained by the above-mentioned X-ray diffraction of the lithium transition metal composite oxide is preferably greater than 0.2° and less than 0.8°. If the half-value width is within the above range, the layered structure can be made into a state with moderate deformation in the plane direction, thereby enabling the high capacity of the battery to be achieved. In the case of less than 0.2°, although the layered structure is very stable in the state before charge and discharge, after the charging process, the layered structure becomes unstable compared to the case where the half-value width is within the above range. After the discharge process, the layered structure becomes more unstable, and the charge and discharge capacity and charge and discharge efficiency are reduced. In addition, in the case of exceeding 0.8°, the deformation of the layered structure is too large, the layered structure becomes brittle, and the charge and discharge capacity and charge and discharge efficiency are reduced.

[0061] Next, the integrated intensity I of the above diffraction peak is 108 / I 110 A method for producing a lithium transition metal composite oxide (positive electrode active material) having a molecular weight of less than 0.4 will be described.

[0062] As an example of an embodiment, a manufacturing process of a positive electrode active material includes: (1) a process of mixing a sodium raw material, a nickel raw material, a manganese raw material, and a raw material of an additive element X and calcining them to synthesize a sodium composite oxide; and (2) a process of reacting the sodium composite oxide with a lithium compound to ion-exchange at least a portion of the Na in the sodium composite oxide with Li.

[0063] This method can obtain a layered rock salt structure with less disorder compared to a method of synthesizing a lithium-containing composite oxide from a lithium raw material.

[0064] As the sodium raw material, at least one of sodium (metallic sodium) and a sodium compound is used. As the sodium compound, there is no particular limitation as long as it is a compound containing sodium, and examples thereof include acetates such as CH3COONa and CH3COONa·3H2O, nitrates such as NaNO3, sulfates such as Na2SO4, carbonates such as Na2CO3, bicarbonates such as NaHCO3, hydroxides such as NaOH, oxides such as Na2O and Na2O2, etc. Among them, Na2CO3, NaHCO3, NaOH, and NaNO3 are particularly preferred.

[0065] As the nickel raw material, at least one of nickel (metallic nickel) and a nickel compound is used. As the nickel compound, there is no particular restriction as long as it is a compound containing nickel, for example, oxides such as NiO, hydroxides such as NiOH, Ni(OH)2, NiOOH, nitrates such as NiNO3, carbonates such as NiCO3, Ni4CO3(OH)6(H2O)4, sulfates such as NiSO4, etc. can be cited. Among them, Ni(OH)2 is particularly preferred.

[0066] As the manganese raw material, at least one of manganese (metallic manganese) and a manganese compound is used. As the manganese compound, there is no particular limitation as long as it is a compound containing manganese, and examples thereof include oxides such as MnO, Mn2O3, Mn3O4, and MnO2, hydroxides such as Mn(OH)2 and MnOOH, carbonates such as MnCO3, nitrates such as Mn(NO3)2, and sulfates such as MnSO4. Among them, Mn(OH)2 is particularly preferred.

[0067] As the raw material of the additive element X, similar to the above-mentioned nickel raw material and manganese raw material, at least one of X and a compound of X is used. The compound is not particularly limited as long as it contains X, and examples thereof include oxides, hydroxides, carbonates, nitrates, sulfates, and the like.

[0068] As the nickel, manganese and X raw materials, the above-mentioned compounds can be used, but a compound containing nickel and manganese, a compound containing nickel, manganese and X, a compound containing nickel and X, and a compound containing manganese and X can also be used.

[0069] The mixing ratio of these raw materials can be appropriately set, preferably to form a composition of Na γ Ni 1-b-c Mn b X c O d (wherein, 0.8≤γ≤1.20, 0.25<b≤0.65, 0≤c≤0.1, 0.4≤1-bc<0.75, d is a value satisfying the atomic valence) The raw materials can be mixed in a manner to obtain a chemical composition represented by the formula. In addition, the method for mixing the raw materials is not particularly limited as long as they can be uniformly mixed, and mixing using a known mixer such as a stirrer can be exemplified.

[0070] The mixture is fired in the atmosphere or in an oxygen flow. The firing temperature is preferably 600 to 1100° C., more preferably 700 to 1000° C. The firing time is preferably 1 to 50 hours when the firing temperature is 600 to 900° C., and preferably 1 to 10 hours when the firing temperature is 900 to 1000° C. Furthermore, there is no particular limitation on the cooling method, for example, natural cooling (cooling in a furnace). After cooling, the fired product is pulverized by a known method to obtain a sodium composite oxide.

[0071] As a preferred method for the ion exchange process of Na to Li in the sodium composite oxide, for example, a method of adding a molten salt bed of a lithium salt to the sodium composite transition metal oxide and heating it can be cited. The lithium salt is preferably at least one selected from lithium nitrate, lithium sulfate, lithium chloride, lithium carbonate, lithium hydroxide, lithium iodide and lithium bromide.

[0072] The heating temperature during the treatment in the ion exchange process is preferably 200 to 400°C, more preferably 250 to 350°C. If the heating temperature at this time exceeds 400°C, the reaction proceeds rapidly and an uneven reaction may occur. In addition, if the heating temperature is lower than 200°C, it may be difficult to fully react. The treatment time is preferably 1 to 50 hours, more preferably 2 to 20 hours, and further preferably 2 to 10 hours. In addition, there is no particular limitation on the cooling method, such as natural cooling (cooling in the furnace). After cooling, the obtained product is fully washed with water, ethanol or methanol, etc., and dried, thereby obtaining a lithium transition metal composite oxide. Furthermore, the atmosphere during drying is preferably in the air or in a vacuum, without particular limitation. In addition, the heat treatment can be performed again after washing.

[0073] [negative electrode]

[0074] The negative electrode 12 has a negative electrode current collector and a negative electrode mixture layer formed on both sides of the negative electrode current collector. The negative electrode current collector can use a foil of a metal such as copper or a copper alloy that is stable within the potential range of the negative electrode 12, a thin film having the metal disposed on the surface, and the like. The negative electrode mixture layer contains a negative electrode active material and a binding material. The negative electrode 12 can be manufactured by coating a negative electrode mixture slurry containing a negative electrode active material, a binding material, etc. on the surface of the negative electrode current collector, drying the coating film, and then rolling it to form a negative electrode mixture layer on both sides of the negative electrode current collector.

[0075] The negative electrode active material contained in the negative electrode mixture layer is not particularly limited as long as it is a material that can reversibly absorb and release lithium ions, and generally, carbon materials such as graphite are used. Graphite can be any of natural graphites such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite, and artificial graphites such as graphitized mesophase carbon microbeads. In addition, as the negative electrode active material, metals such as Si and Sn alloyed with Li, metal compounds containing Si, Sn, etc., lithium-titanium composite oxides, etc. can be used. In addition, materials with a carbon coating provided on these can be used. For example, SiO x (0.5≤x≤1.6) represented by Si-containing compounds, or Li 2y SiO (2+y) A Si-containing compound in which Si fine particles are dispersed in a lithium silicate phase represented by (0<y<2) or the like can be used together with graphite.

[0076] The binder contained in the negative electrode mixture layer can be PTFE, PVdF and other fluorine-containing resins, PAN, polyimide, acrylic resin, polyolefin, etc., and preferably styrene-butadiene rubber (SBR) as in the case of the positive electrode 11. In addition, the negative electrode mixture layer can contain CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc.

[0077] [Diaphragm]

[0078] The separator 13 uses, for example, a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, and the like. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, and the like are preferred. The separator 13 may be a single-layer structure or a laminated structure. In addition, a resin layer having high heat resistance such as aramid resin or a filler layer containing a filler of an inorganic compound may be provided on the surface of the separator 13.

[0079] Example

[0080] Hereinafter, the present disclosure will be further described by way of examples, but the present disclosure is not limited to these examples.

[0081] <Example 1>

[0082] [Preparation of positive electrode active material]

[0083] A hydroxide containing Ni and Mn in a molar ratio of 1:1 is mixed with sodium carbonate in a molar ratio of Ni:Mn:Na=0.5:0.5:1.05, and the obtained mixture is heated at a heating rate of 1°C / min, calcined in air at 800°C for 24 hours, and then quenched in air to obtain a composite oxide containing Na. Then, lithium nitrate and lithium chloride are mixed in a molar ratio of LiNO3:LiCl=88:12 to prepare a molten salt containing Li. The Li-containing molten salt and the above-mentioned Na-containing compound are mixed in a molar ratio of Li:Na=30:1, and the obtained mixture is heated at a heating rate of 5°C / min, heated in air at 280°C for 5 hours, and cooled at a cooling rate of 2°C / min to obtain a Li-Na mixture. The Li-Na mixture is washed with a sufficient amount of water, heated at 160°C in a vacuum for 4 hours to obtain a lithium transition metal composite oxide. As described above, in Example 1, a lithium transition metal composite oxide was obtained by using the production method disclosed herein, which includes the steps of synthesizing a sodium composite oxide and ion-exchanging at least a portion of Na in the sodium composite oxide with Li.

[0084] The lithium transition metal composite oxide of Example 1 was subjected to X-ray diffraction measurement. Figure 2 The overall view and the 60-70° magnified view of the X-ray diffraction results of the lithium transition metal composite oxide of Example 1 are shown. In addition, the integrated intensity I of the diffraction peak of the (108) plane of the X-ray diffraction pattern obtained by X-ray diffraction is 108 The integrated intensity I of the diffraction peak relative to the (110) plane 110 Ratio I 108 / I 110 In addition, the integrated intensity I of the diffraction peak of the (003) plane of the X-ray diffraction pattern is003 The integrated intensity I of the diffraction peak relative to the (104) plane 104 Ratio I 003 / I 104 The half-value widths of the diffraction peaks of the (108) plane and the (110) plane in the X-ray diffraction pattern were 0.33° and 0.45°, respectively.

[0085] In addition, the disorder amount of the lithium transition metal composite oxide of Example 1 was calculated based on the Rietveld analysis results of the X-ray diffraction pattern. Specifically, the X-ray analysis comprehensive software SmartLabStudio II manufactured by Rigaku Corporation was used to calculate based on the above X-ray diffraction pattern. As a result, the disorder amount of the lithium transition metal composite oxide of Example 1 was 5.0%.

[0086] [Production of positive electrode]

[0087] The positive electrode active material: acetylene black: polyvinylidene fluoride are mixed in a mass ratio of 92:5:3, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode paste. The positive electrode paste is applied to an aluminum foil, and after the coating is dried, the coating is rolled using a calendering roller to prepare a positive electrode having a positive electrode mixture layer formed on the positive electrode collector.

[0088] [Preparation of non-aqueous electrolyte]

[0089] Lithium hexafluorophosphate (LiPF6) was dissolved at a concentration of 1 mol / L in a mixed solvent of fluoroethylene carbonate (FEC) and methyl propionate (FMP) at a volume ratio of 1:3 to prepare a non-aqueous electrolyte.

[0090] [Production of test unit]

[0091] The positive electrode and the lithium metal serving as the negative electrode are stacked in a manner opposing each other via a separator, the stacked electrode body and the non-aqueous electrolyte are housed in a coin-shaped outer can, the opening of the outer can is sealed with a gasket and a sealing body, and a test unit (non-aqueous electrolyte secondary battery) is manufactured.

[0092] [Evaluation of charge and discharge efficiency]

[0093] For the above test unit, constant current charging was performed at 0.2C constant current to 4.5V at 25°C, and then constant voltage charging was performed at 4.5V until the current value reached 0.02C. After 20 minutes of rest, constant current discharge was performed at 0.2C constant current to 2.5V, and then rested for 20 minutes. Based on the charge capacity and discharge capacity measured in the above charge and discharge, the charge and discharge efficiency was calculated by the following formula.

[0094] Charge and discharge efficiency (%) = discharge capacity / charge capacity × 100

[0095] <Example 2>

[0096] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1, aluminum nitrate nonahydrate, and sodium carbonate were mixed at a molar ratio of Ni:Mn:Al:Na=0.4975:0.4975:0.005:1.05, and a test unit was prepared in the same manner as in Example 1, and measurements and evaluations were performed. The X-ray diffraction results of the lithium transition metal composite oxide of Example 2 are shown in Figure 3 .

[0097] <Example 3>

[0098] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1, aluminum nitrate nonahydrate, and sodium carbonate were mixed at a molar ratio of Ni:Mn:Al:Na=0.495:0.495:0.01:1.05, and a test unit was prepared in the same manner as in Example 1, and measurements and evaluations were performed. The results of X-ray diffraction of the lithium transition metal composite oxide of Example 3 are shown in Figure 4 .

[0099] <Example 4>

[0100] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1, aluminum nitrate nonahydrate, and sodium carbonate were mixed at a molar ratio of Ni:Mn:Al:Na=0.4875:0.4875:0.025:1.05, and a test unit was prepared in the same manner as in Example 1, and measurements and evaluations were performed. The results of X-ray diffraction of the lithium transition metal composite oxide of Example 4 are shown in Figure 5 .

[0101] <Example 5>

[0102] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1, cobalt nitrate hexahydrate, and sodium carbonate were mixed at a molar ratio of Ni:Mn:Co:Na=0.492:0.492:0.016:1.05, and a test unit was prepared in the same manner as in Example 1, and measurements and evaluations were performed. The results of X-ray diffraction of the lithium transition metal composite oxide of Example 5 are shown in Figure 6 .

[0103] <Example 6>

[0104] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1, cobalt nitrate hexahydrate, and sodium carbonate were mixed at a molar ratio of Ni:Mn:Co:Na=0.4845:0.4845:0.031:1.05, and a test unit was prepared in the same manner as in Example 1, and the measurement and evaluation were performed. The results of X-ray diffraction of the lithium transition metal composite oxide of Example 6 are shown in Figure 7 .

[0105] <Example 7>

[0106] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn in a molar ratio of 1:1, zirconium oxide, and sodium carbonate were mixed in a molar ratio of Ni:Mn:Zr:Na=0.4975:0.4975:0.005:1.05, and a test unit was prepared in the same manner as in Example 1, and measurements and evaluations were performed. The results of X-ray diffraction of the lithium transition metal composite oxide of Example 7 are shown in Figure 8 .

[0107] <Example 8>

[0108] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn in a molar ratio of 1:1, sodium phosphate, and sodium carbonate were mixed in a molar ratio of Ni:Mn:P:Na=0.4975:0.4975:0.005:1.05, and a test unit was prepared in the same manner as in Example 1, and measurements and evaluations were performed. The results of X-ray diffraction of the lithium transition metal composite oxide of Example 8 are shown in Fig. 9 .

[0109] <Example 9>

[0110] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn in a molar ratio of 1:1, sodium phosphate, and sodium carbonate were mixed in a molar ratio of Ni:Mn:P:Na=0.495:0.495:0.01:1.05, and a test unit was prepared in the same manner as in Example 1, and measurements and evaluations were performed. The results of X-ray diffraction of the lithium transition metal composite oxide of Example 9 are shown in Fig.10 .

[0111] <Example 10>

[0112] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 46:54 and sodium carbonate were mixed at a molar ratio of Ni:Mn:Na=0.46:0.54:1.05, and a test unit was prepared in the same manner as in Example 1, and measurements and evaluations were performed. The results of X-ray diffraction of the lithium transition metal composite oxide of Example 10 are shown in Fig.11 .

[0113] <Example 11>

[0114] In the preparation of the positive electrode active material, the test unit was prepared in the same manner as in Example 1 except that the Li-containing molten salt and the Na-containing compound were mixed at a molar ratio of Li:Na=5:1. The measurement and evaluation were performed. The results of X-ray diffraction of the lithium transition metal composite oxide of Example 11 are shown in Fig.12 .

[0115] <Example 12>

[0116] In the preparation of the positive electrode active material, a Li-containing molten salt and a Na-containing compound were mixed at a molar ratio of Li:Na=5:1, and the obtained mixture was heated at a heating rate of 5°C / min, heated in air at 350°C for 5 hours, and cooled at a cooling rate of 2°C / min to obtain a Li-Na mixture. A test unit was prepared in the same manner as in Example 1, and the measurements and evaluations were performed. Furthermore, the results of X-ray diffraction of the lithium transition metal composite oxide of Example 12 are shown in Fig.13 .

[0117] <Comparative Example 1>

[0118] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn in a molar ratio of 1:1 and lithium hydroxide in a molar ratio of Ni:Mn:Li=0.5:0.5:1.05 are mixed, and the resulting mixture is heated at a heating rate of 5°C / min, calcined at 900°C in air for 10 hours, and cooled at a cooling rate of 10°C / min to obtain a lithium transition metal composite oxide. In addition to the preparation of the positive electrode active material, a test unit is prepared in the same manner as in Example 1, and measurements and evaluations are performed. Furthermore, the results of X-ray diffraction of the lithium transition metal composite oxide of Comparative Example 1 are shown in Fig.14 .

[0119] <Comparative Example 2>

[0120] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1, aluminum nitrate nonahydrate, and sodium carbonate were mixed at a molar ratio of Ni:Mn:Al:Na=0.4975:0.4975:0.005:1.05, and a test unit was prepared in the same manner as in Comparative Example 1, and measurements and evaluations were performed. The X-ray diffraction results of the lithium transition metal composite oxide of Comparative Example 2 are shown in Fig.15 .

[0121] <Comparative Example 3>

[0122] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1, aluminum nitrate nonahydrate, and sodium carbonate were mixed at a molar ratio of Ni:Mn:Al:Na=0.492:0.492:0.016:1.05, and a test unit was prepared in the same manner as in Comparative Example 1, and measurements and evaluations were performed. The X-ray diffraction results of the lithium transition metal composite oxide of Comparative Example 3 are shown in Fig.16 .

[0123] <Comparative Example 4>

[0124] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1, aluminum nitrate nonahydrate, and sodium carbonate were mixed at a molar ratio of Ni:Mn:Al:Na=0.4845:0.4845:0.031:1.05, and a test unit was prepared in the same manner as in Comparative Example 1, and measurements and evaluations were performed. The X-ray diffraction results of the lithium transition metal composite oxide of Comparative Example 4 are shown in Fig.17 .

[0125] <Comparative Example 5>

[0126] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1 and sodium hydroxide were mixed at a molar ratio of Ni:Mn:Li=0.5:0.5:1.01. The test unit was prepared in the same manner as in Comparative Example 1, and the measurements and evaluations were performed. The X-ray diffraction results of the lithium transition metal composite oxide of Comparative Example 5 are shown in Fig.18 .

[0127] <Comparative Example 6>

[0128] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1, cobalt nitrate hexahydrate, and sodium hydroxide were mixed at a molar ratio of Ni:Mn:Co:Li=0.4845:0.4845:0.031:1.01, and a test unit was prepared in the same manner as in Comparative Example 1, and measurements and evaluations were performed. The X-ray diffraction results of the lithium transition metal composite oxide of Comparative Example 6 are shown in Fig.19 .

[0129] <Comparative Example 7>

[0130] In the preparation of the positive electrode active material, a hydroxide containing Ni and Mn at a molar ratio of 1:1, cobalt nitrate hexahydrate, and sodium hydroxide were mixed at a molar ratio of Ni:Mn:Co:Li=0.4685:0.4685:0.063:1.01, and a test unit was prepared in the same manner as in Comparative Example 1, and measurements and evaluations were performed. The X-ray diffraction results of the lithium transition metal composite oxide of Comparative Example 7 are shown in Fig. 20 .

[0131] The charge capacity, discharge capacity, and charge / discharge efficiency of the Examples and Comparative Examples are shown in Table 1. Table 1 also shows the ratio of the metal elements and the integrated intensity I of the diffraction peak of the (108) plane in the X-ray diffraction pattern obtained by X-ray diffraction. 108 The integrated intensity I of the diffraction peak relative to the (110) plane 110 Ratio I 108 / I 110 The integrated intensity of the diffraction peak of the (003) plane is 003 The integrated intensity I of the diffraction peak relative to the (104) plane 104 Ratio I 003 / I 104 , the half-value width and disorder amount of the diffraction peaks of the (108) plane and the (110) plane.

[0132] Table 1

[0133]

[0134] As shown in Table 1, the charge capacity, discharge capacity, and charge-discharge efficiency of the test cells of Examples 1 to 12 are higher than those of Comparative Examples 1 to 7. In addition, in addition to Ni and Mn, the charge capacity, discharge capacity, and charge-discharge efficiency of Examples 2 to 4 to which Al is added, Example 5 to which Co is added, and Examples 8 and 9 to which P is added tend to be higher than those of Example 1 to which Al, Co, or P is not added. In addition, by changing the conditions of the process of ion-exchanging at least a portion of the Na of the sodium composite oxide with Li, the charge capacity, discharge capacity, and charge-discharge efficiency of the test cells of Examples 11 and 12 tend to be higher than those of the test cell of Example 1.

[0135] The SEM images of the lithium transition metal composite oxides prepared in Example 1 and Comparative Example 1 are shown in FIG. Fig.21 and Fig. 22 Furthermore, all SEM images were taken at a magnification of 5000 times. Fig.21 and Fig. 22 As shown, the lithium transition metal composite oxides prepared in Example 1 and Comparative Example 1 are both substantially spherical particles. In addition, the SEM image confirmed that the lithium transition metal composite oxide of Example 1 has finer primary particles than the lithium transition metal composite oxide of Comparative Example.

[0136] The present disclosure is further described by the following embodiments.

[0137] Technical composition 1: A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a composition formula Li α Na β Ni 1-b-cMn b X c O d (wherein X is at least one element selected from metal elements other than Li, Na, Ni, and Mn, 0.80≤α≤1.20, 0≤β≤0.05, 0.80≤α+β≤1.20, 0.25<b≤0.65, 0≤c≤0.1, 0.4≤1-bc<0.75, and d is a value satisfying the atomic valence) represented by a lithium transition metal composite oxide, wherein the integrated intensity I of the diffraction peak of the (108) plane of the X-ray diffraction pattern of the lithium transition metal composite oxide obtained by powder X-ray diffraction 108 The integrated intensity I of the diffraction peak relative to the (110) plane 110 Ratio I 108 / I 110 For I 108 / I 110 <0.4.

[0138] Technical configuration 2: The positive electrode active material for a non-aqueous electrolyte secondary battery according to technical configuration 1, wherein the composition formula is Li α Na β Ni 1-b-c Mn b X c O d In the above, X is at least one element selected from Mg, Ca, Sr, Ba, Sn, Ti, Si, V, Cr, Fe, Cu, Zn, Bi, Sb, B, Ga, In, P, Zr, Hf, Nb, Ta, Mo, W, Co, and Al.

[0139] Technical configuration 3: The positive electrode active material for a non-aqueous electrolyte secondary battery according to technical configuration 1 or 2, wherein the composition formula is Li α Na β Ni 1-b-c Mn b X c O d In the above, X is Al or Co or Zr or P.

[0140] Technical configuration 4: The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of technical configurations 1 to 3, wherein the integrated intensity I of the diffraction peak of the (003) plane of the X-ray diffraction pattern is 003 The integrated intensity I of the diffraction peak relative to the (104) plane 104 Ratio I 003 / I 104 For I 003 / I 104 >1.0.

[0141] Technical Configuration 5: The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Technical Configurations 1 to 4, wherein the half-value widths of the diffraction peaks of the (108) plane and the (110) plane in the X-ray diffraction pattern are 0.2° or more and 0.8° or less.

[0142] Technical configuration 6: The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of technical configurations 1 to 5, wherein the composition formula is Li α Na β Ni 1-b-c Mn b X c O d In the above method, the molar ratio (y) of Na is 0≤y≤0.035.

[0143] Technical composition 7: A method for manufacturing a positive electrode active material for a non-aqueous electrolyte secondary battery, comprising: synthesizing a composition formula Na γ Ni 1-b-c Mn b X c O d (wherein X is at least one element selected from metal elements other than Li, Na, Ni, and Mn, 0.80≤γ≤1.20, 0.25<b≤0.65, 0≤c≤0.1, 0.4≤1-bc<0.75, and d is a value satisfying the atomic valence); and a process of reacting the sodium composite oxide with a lithium compound to exchange at least a portion of the Na ions of the sodium composite oxide with Li.

[0144] Technical configuration 8: A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the positive electrode comprises the positive electrode active material according to any one of technical configurations 1 to 6.

[0145] Description of Reference Numerals

[0146] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plates, 20 positive electrode lead, 21 negative electrode lead, 22 slotted portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket.

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a composition formula Li α Na β Ni 1-b-c Mn b X c O d A lithium transition metal composite oxide represented by the formula, wherein X is at least one element selected from metal elements other than Li, Na, Ni, and Mn, 0.80≤α≤1.20, 0≤β≤0.05, 0.80≤α+β≤1.20, 0.25<b≤0.65, 0≤c≤0.1, 0.4≤1-bc<0.75, d is a value satisfying the atomic valence, The integrated intensity I of the diffraction peak of the (108) plane of the X-ray diffraction pattern of the lithium transition metal composite oxide obtained by powder X-ray diffraction is 108 The integrated intensity I of the diffraction peak relative to the (110) plane 110 Ratio I 108 / I 110 For I 108 / I 110 <0.

4.

2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, In the composition formula Li α Na β Ni 1-b-c Mn b X c O d In the above, X is at least one element selected from Mg, Ca, Sr, Ba, Sn, Ti, Si, V, Cr, Fe, Cu, Zn, Bi, Sb, B, Ga, In, P, Zr, Hf, Nb, Ta, Mo, W, Co, and Al.

3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, In the composition formula Li α Na β Ni 1-b-c Mn b X c O d In the above, X is Al or Co or Zr or P.

4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, The integrated intensity I of the diffraction peak of the (003) plane of the X-ray diffraction pattern is 003 The integrated intensity I of the diffraction peak relative to the (104) plane 104 Ratio I 003 / I 104 For I 003 / I 104 >1.

0.

5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, The half-value widths of the diffraction peaks of the (108) plane and the (110) plane of the X-ray diffraction pattern are not less than 0.2° and not more than 0.8°.

6. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, In the composition formula Li α Na β Ni 1-b-c Mn b X c O d In the above, the molar ratio β of Na is 0≤y≤0.

035.

7. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, comprising: Synthesis of the composition Na γ Ni 1-b-c Mn b X c O d The process of producing a sodium composite oxide represented by the formula, wherein X is at least one element selected from metal elements other than Li, Na, Ni, and Mn, 0.80≤γ≤1.20, 0.25<b≤0.65, 0≤c≤0.1, 0.4≤1-bc<0.75, and d is a value satisfying the atomic valence; and A step of reacting the sodium composite oxide with a lithium compound to ion-exchange at least a portion of Na in the sodium composite oxide with Li.

8. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode includes the positive electrode active material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Lithium-nickel-manganese-cobalt multiple oxide and lithium-ion secondary battery using the same as positive electrode active material

    JP2005053764A